The Alternative Concepts of Blasphemy Law in Indonesia: Legal Comparison with Ireland and Canada - Loresta Cahyaning Lintang; Adriano Martufi; J.W. Ouwerker (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2021)
Indonesia has recognized and implemented blasphemy law within its legal system. Nevertheless, by many scholars, it is considered ambiguous and